Red leaf, yellow leaf - Ehlert, Lois. (San Diego : Harcourt Brace, 1991)
A child describes the growth of a maple tree from seed to sapling.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
3.3.
3.3
K-3
Keywords: Trees -- Fiction; Trees -- Fiction